2017
DOI: 10.1093/ije/dyw264
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Profile: Stress in Pregnancy (SIP) Study

Abstract: to understand the extent to which an adverse environment in utero can alter fetal growth and development, with potential lifelong impacts on health and disease, based on the theoretical framework of the 'Developmental Origins of Health and Diseases (DoHaD) Hypothesis'. [1][2][3][4][5][6] Growing evidence [7][8][9] suggests that not only the genome but also the epigenome, the heritable, quasi-stable yet dynamic control of gene expression, can be modulated by the environment, and plays a vital role in defining h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 56 publications
0
35
0
Order By: Relevance
“…The demographic and clinical characteristics of the RICHS [5] and SIP study [38] populations have been previously described and are summarized in Table 2. Briefly, the RICHS study population is predominately Caucasian (78.2%), with SGA, AGA and LGA infants constituting approximately 20%, 56% and 24%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The demographic and clinical characteristics of the RICHS [5] and SIP study [38] populations have been previously described and are summarized in Table 2. Briefly, the RICHS study population is predominately Caucasian (78.2%), with SGA, AGA and LGA infants constituting approximately 20%, 56% and 24%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As the RICHS population is predominantly Caucasian (78%) and oversampled for SGA and LGA infants, we conducted a replication study in the Stress in Pregnancy (SIP) study [38], an on-going urban birth cohort that is more ethnically diverse and has a birth weight distribution comparable to general population. The current study includes mother-infant pairs recruited from prenatal clinics at the Icahn School of Medicine at Mount Sinai, New York Hospital of Queens and Queens College with available placental RNA.…”
Section: Methodsmentioning
confidence: 99%
“…The sample set came from 75 newborns whose mothers participated in a longitudinal birth cohort recruited at the prenatal obstetrics and gynecology clinics at Mount Sinai Hospital and New York Presbyterian/Queens Hospital. A detailed description of the population is published in Finik and Nomura (). Both sites serve predominantly low‐income ethnic minority populations residing in New York City.…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria for participation included HIV infection, maternal psychosis, maternal age < 15 years, life-threatening maternal medical complications, and congenital or chromosomal abnormalities in the fetus. A detailed description of the study can be found elsewhere (Finik and Nomura, 2017). Demographic information, including maternal education, marital status, race, and age was reported by participants during the second trimester (Table 1).…”
Section: Methodsmentioning
confidence: 99%